Workshop Penulisan Jurnal Ilmiah Guru SMA-SMK Pinggir Kabupaten Bengkalis - Isjoni; Riantama, M. Yogi; Nas, Sakdanur (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
This service aims to provide understanding and experience about writing scientific journalsin the form of articles to high school teachers in Pinggir District, Bengkalis Regency.Hopefully, with this service, all SMA-SMK teachers in Pinggir District, Bengkalis Regency,can later carry out journal writing as a teacher's scientific work. This service targetsteachers whose promotion is constrained due to the absence of research in their scientificwork. It is concluded that many teachers still do not understand the nature of writing thisjournal. This is because teachers are generally not used to writing articles for journals.However, the enthusiasm of SMP-SMA teachers in participating in the service activities isrelatively high, and the questions that are conveyed to the resource persons are relativelyactive and hit the targets of the PTK itself. Most of the initial and final activities for 4 days(32 hours) understand, and the motivation to produce products is relatively high. No onedoes not understand when carrying out activities, and sincerity is seen from time to time inboth group and classical discussions. At the end of the service activity, each teacher isrequired to prepare a product in the form of a proposal, which consists of Chapter IIntroduction, Chapter II Literature Review, and Chapter III Research Methods. AndBibliography. Of the 30 teachers, only five have submitted articles to be published in thejournal.